PERSEPSI PESERTA DIDIK SMA MENGENAI KUALITAS MEDIA PEMBELAJARAN BAHASA INDONESIA - Winda Pangestika; Ika Septiana; Icuk Prayogi (JS (JURNAL SEKOLAH), 2022)
Abstract. This research conducted to determine the perception of high school students regarding the quality of Indonesian learning. From that, the researcher formulated the statement of the problem in this study is how the perceptions of high school students regarding the quality of Indonesian language learning media. This research was aimed at describing students' perceptions of the quality of Indonesian language learning media. This study used descriptive qualitative method. The data collection method used in this study is documentation and interviews with listening and note-taking techniques. The listening technique was carried out to listen to the perceptions of high school students regarding the quality of Indonesian language learning media. The note-taking technique is to record several forms of relevance to the research from the learning process. The interview was conducted in order to determine the students' perceptions of the quality of Indonesian language learning media. Based on the results of the research, there are 36 students' perceptions of them were found. First, the online learning process is less effective because students cannot interact directly in the learning process. Second, face-to-face learning are disturbed by the weakening of the internet signal. Third, face-to-face learning is more effective than online.Keywords : Learners, online learning, pandemic, perception Abstrak.Penelitian ini dilatar belakangi untuk mengetahui persepsi peserta didik SMA mengenai kualitas pembelajaran Bahasa Indonesia. Rumusan masalah dalam penelitian ini ialah bagaimanakah perspesi peserta didik SMA mengenai kualitas media pembelajaran Bahasa Indonesia? Adapun tujuan penelitian ini untuk mendeskripsikan persepsi peserta didik mengenai kualitas media pembelajaran Bahasa Indonesia. Penelitian ini menggunakan metode deskriptif kualitatif. Metode pengumpulan data yang digunakan ialah metode dokumentasi dan wawancara dengan teknik simak dan teknik catat. Teknik simak dilakukan untuk menyimak persepsi peserta didik SMA mengenai kualitas media pembelajaran Bahasa Indonesia. yang akan diteliti. Teknik catat adalah mencatat beberapa bentuk revelan bagi penelitiannya dari proses pembelajaran. Wawancara tersebut dilakukan agar mengetahui persepsi peserta didik mengenai kualitas media pembelajaran Bahasa Indonesia. Berdasarkan hasil penelitian Persepsi Peserta Didik SMA mengenai kualitas Pembelajaran Bahasa Indonesia di temukan 36 persepsi peserta didik diantaranya. Pertama proses pembelajaran secara daring kurang efektif, dikarenakan peserta didik tidak dapat berinteraksi langsung dalam proses pembelajaran. Kedua pembelajaran tatap muka, peserta didik terganggu oleh melemahnya sinyal internet. Ketiga pembelajaran secara offline lebih efektif dari pada online.Kata Kunci : Peserta didik, pembelajaran daring, pandemi, persepsi